CRYPTOSPORIDIOSIS IN SULAIMANI PEDIATRIC TEACHING HOSPITAL AND COMPARISON OF DIFFERENT DIAGNOSTIC METHODS FOR ITS DETECTION - Mohammed Ali, Fatimah; Kader Ali, Shahnaz Abdul (European Scientific Journal, ESJ, 2013)
The present study aimed to investigate the presence and prevalence of Cryptosporidium among children in Sulaimani Pediatric Teaching Hospital and to determine the best method for its diagnosis. The study started from the 1st of Jun. to the 1st of Sept. 2012. Two hundred fifty stool samples were collected from children of 6 month to 12 years of age from both genders who attended the hospital. Stool samples were inspected by modified acid-fast stain as a standard method, direct wet mount, Crypto-Strips method and enzyme linked immunosorbant assy (ELISA). Modified Ziehl-Neelsen technique revealed 38 (15.2%) positive cases for Cryptosporidium oocysts, of 22 males and 16 females, 4-6 years of age group was more susceptible to infection with Cryptosporidium and highly significant relationship was found between the genders and between different age groups of infection with a highly significant difference between rural and urban area. The highest rate of infection was found in the soft type of stool samples with a significant difference between them. The prevalence of Cryptosporidium was 13.6% by using direct wet mount, 6.8%, for ELISA and 4.4% by Crypto-Strips method in comparison with MZN method. It is concluded that cryptosporidiosis found to be endemic in Sulaimani city for the first time and the modified acid-fast stain was the most reliable technique for its diagnosis.